KONSELING BEVAHIORAL DENGAN TEKNIK ROLE PLAYING MELALUI LESSON STUDY UNTUK MENINGKATKAN SELF AFILIASI - Jayanti, Ni Kadek Dwi; Dantes, Nyoman; Dharsana, I Ketut (Universitas Pendidikan Ganesha, 2019)
This study was aimed to determine the effectiveness of the implementation of behavioral counseling theory by using role playing technique to improve student self-affiliation, and to know the difference of self-affiliation between the students who were given behavioral counseling by using role playing technique and the students who were not given in which the students were grade VIII students of SMP Lab Undiksha Singaraja. The population of this research was all students of grade VIII SMP Lab Undiksha Singaraja. The sample of this research was determined by random sampling technique. The methods of data collection in this study used the observation methods, interviews, diaries and self-affiliated scheme questionnaires of Likert scale. The data analysis method for the hypothesis test used the t-test. The results of this study indicated that there was effectiveness of behavioral counseling theory by using role playing technique to improve self-affiliation of grade VIII students of Undiksha SMP Lab Undiksha Singaraja and there were differences of self-affiliation between the students who were given behavioral counseling by using role playing technique and the students who were not given. Keywords: Behavioral Counseling, Role Playing Technique, Self-affiliation